INTRAFAMILIAL AND MIDPARENTAL-CHILD CORRELATIONS AND HERITABILITY ESTIMATES OF ANTHROPOMETRIC MEASUREMENTS IN PRADER-WILLI SYNDROME FAMILIES - Butler, Merlin G. (Dysmorphol Clin Genet, 1990)
To determine the effects of familial background on anthropometric dimensions in Prader-Willi syndrome (PWS), we measured weight; height; sitting height; longitude and breadth of the head, hands, and feet; head, arm, and calf circumferences; and triceps and subscapular skinfolds in 28 individuals with the syndrome and their natural parents. Midparental-child correlations were significant for height and foot length, with heritability estimates of 0.52 and 0.68, respectively. Significant mother-child correlations were found for weight, height, foot length, and minimal frontal diameter for the total group; in addition, hand length and breadth, and calf and arm circumferences were significant for the patients age 12.5 years or under. These data provide evidence for maternal effects on several physical characteristics in PWS, particularly in younger patients.